Effect of Using Mind Maps on Understanding Islamic Education Curriculum - Abdul Hamid Ibrahim; Saleh Al-Azmey (International Journal of Instructional Technology and Educational Studies)
Relaying on Teaching Islamic Education Curriculum, The Researcher Realized That The Subject Is Taught By A Classical Styles Depending on Dictation By Teachers, Hence Students' Lack In Motivation Towards It. Thus, The Researcher Tried To Increase The Effectiveness of Teaching The Subject By Using Mind Maps. The Research Sample Included (50) Students in Prep Stage of Islamic Education Class. The Researcher Prepared An Approach Measure Towards Islamic Education Containing (40) Positive \ Negative Clauses Distributed To (3) Axes Controlled By Relative Importance And Experts' Opinions. Results Showed Statistically Significant Differences Between The Pre \ Post Applications of The Experiment Group In Approach Test At The Favor of The Post Application.